IGF1R immunohistochemistry in Ewing’s sarcoma as predictor of response to targeted therapy - Gonzalez, Elizabeth; Bui, Marilyn; Ahmed, Atif (International Journal of Health Sciences, 2020)
Objectives: Ewing’s sarcoma is an aggressive malignancy of bone and soft tissue in children and young adults. Despite advances in modern therapy, metastasis can occur and results in high mortality. The objective of this study was to identify whether the signaling transduction proteins, insulin growth factor receptor (IGF1R) and S6 kinase (S6K), can predict poor prognosis in Ewing’s sarcoma. Materials and Methods: After the Institutional Research Board approval, immunohistochemical experiments on tissue microarray slides containing 32 archived Ewing’s sarcoma tumor samples were performed with antibodies against IGF1Rβ and p-S6K. Immunohistochemical staining results were correlated with patients’ clinical data including clinical stage and overall survival (OS). Results: Patients had an age range of 12–72 years and 8 (25%) were ≤20 years. After a follow-up to 14 years, the OS ranged from 25 to 5065 days. High expression of IGF1Rβ and p-S6K, defined as staining stronger than positive control, was identified in 25% and 68.75% of cases, respectively. Statistical analysis revealed that IGF1Rβ high expression had a significant association with adverse outcome, shorter OS (P < 0.05), and near significant association with advanced stage tumors (P = 0.0534). Expression of S6K exhibited a trend toward shorter survival (P = 0.0934). Conclusion: High expression or strong staining of IGF1Rβ in Ewing’s sarcoma may be more important than overall positive staining in identifying poor prognosis and aggressive cases to be selected for IGF1R inhibitory therapy. More definitive studies are needed to confirm the role of S6K in the prognosis in Ewing’s sarcoma tumors.